THE FIELD OF PROPER NAMES OF CATERING BUSINESSES IN MOSCOW AND VIETNAM (Journal of Foreign Language Studies, 2019)
The article provides a comparative analysis of the proper names of catering businesses in Moscow and Ho Chi Minh City, thence, sheds light on their formative and semantic differences. The corpus used in the article includes 1,000 names in Ho Chi Minh City and 7,000 names in Moscow collected and selected from newspapers, advertisements, signs and online resources. In particular, this study is critical to the dissemination of the names of catering businesses as well as to a gap in the research. The analysis of corpus concluded that the differences in the proper names of catering businesses can be classified into groups, including diversity of naming and representation of regional names.
Keywords: proper names of businesses; names of catering businesses; semantic; form